The Position of the Public Accountant in the Legal System of Public Accounting - Guaoui, Said (Journal of Legal Studies and Researches, 2026)
The public accountant is considered the most important link in the public accounting control system, which is based on the separation of duties between the authorizing officer and the public accountant. The authorizing officer is responsible for carrying out the financial operations related to the management tasks within the public body he manages. In contrast, a public accountant is always there to monitor the extent to which these financial operations comply with the laws and regulations specific to this field.